Numerical study of prestressing reinforcement position on sleeper response - Řoutil Ladislav; Veselý Václav; Šimonová Hana; Koryčanská Barbora; Keršner Zbyněk (Civil-Comp Press, 2016)
A numerical study of the structural response of the prestressed monoblock railway sleepers used on Czech railway tracks is presented. The build quality of prestressed railway sleepers is assessed using three-point bending tests as stipulated by European Standards. Two sleeper cross-sections are evaluated with respect to static loading. The tests are modelled herein using ATENA nonlinear finite element method (FEM) software. This programme enables the realistic estimation of failure load, pre/postpeak behaviour and crack pattern using non-linear fracture mechanics methods as well as damage and plasticity models. The main purpose of this study is to quantify the influence of prestressing reinforcement position on sleeper response during evaluative tests. A comparison of the simulation results with ex-perimental data is also performed.
Numerical study of prestressing reinforcement position on sleeper response
Keywords: prestressed sleepers; evaluative bending test; load–deflection diagram; numerical model; parametric study; prestressed sleepers; evaluative bending test; load–deflection diagram; numerical model; parametric study